2003
DOI: 10.1038/sj.ijo.0802515
|View full text |Cite
|
Sign up to set email alerts
|

The relation of obesity throughout life to carotid intima-media thickness in adulthood: the Bogalusa Heart Study

Abstract: OBJECTIVE:Although obese children are at increased risk for coronary heart disease in later life, it is not clear if this association results from the persistence of childhood obesity into adulthood. We examined the relation of adiposity at various ages to the carotid intima-media thickness (IMT) at age 35 y. DESIGN: Prior to the determination of IMT by B-mode ultrasound, subjects (203 men, 310 women) had, on average, six measurements of body mass index (BMI) and triceps skinfold thickness (TSF) between the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
151
1
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(176 citation statements)
references
References 46 publications
(68 reference statements)
11
151
1
11
Order By: Relevance
“…The one exception was the study by Wright et al (30) which measured CIMT at age 50 years and showed no association with childhood BMI. Using data from the Bogalusa Heart Study, Freedman et al (37) showed no relationship between childhood BMI status and adult CIMT among adults who were of normal BMI. Interestingly, those in the 90th centile for CIMT actually had lower BMI up to age 7 years.…”
Section: Independent Effects Of Childhood Obesity On Adult Disease Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…The one exception was the study by Wright et al (30) which measured CIMT at age 50 years and showed no association with childhood BMI. Using data from the Bogalusa Heart Study, Freedman et al (37) showed no relationship between childhood BMI status and adult CIMT among adults who were of normal BMI. Interestingly, those in the 90th centile for CIMT actually had lower BMI up to age 7 years.…”
Section: Independent Effects Of Childhood Obesity On Adult Disease Riskmentioning
confidence: 99%
“…There were therefore very few hypertensive cases to consider (16/130 men). Six studies considered the association between childhood BMI and carotid intima media thickness (CIMT) (30,(35)(36)(37)(38)(39) , with five of these studies showing a positive association (35)(36)(37)(38)(39) . However, after adjusting for adult BMI only one positive association remained, and this was for the cumulative change in BMI from childhood to adulthood (39) .…”
Section: Independent Effects Of Childhood Obesity On Adult Disease Riskmentioning
confidence: 99%
“…Low-grade inflammation seems to play a role in the pathogenesis of atherosclerosis from early ages 1,2 suggesting that preventive measures should start early in life. Observational studies have shown that a state of low-grade inflammation is associated with adiposity in children and adolescents, [3][4][5][6] as it has been shown in adults.…”
Section: Introductionmentioning
confidence: 99%
“…7 There is a widely held assumption that childhood obesity is a major risk factor for CVD in adulthood. However, although many studies have shown a positive relationship between childhood obesity and adult CVD risk factors, 8,9 it remains unclear whether childhood obesity exerts an independent effect on adult cardiovascular health. Some studies suggest quite the opposite, with those who were thinnest as children and overweight as adults showing the highest adult metabolic risk profile.…”
Section: Introductionmentioning
confidence: 99%